Anatoxin-a producing Tychonema (Cyanobacteria) in European waterbodies. (1st February 2015) - Shams, S.; Capelli, C.; Cerasino, L.; Ballot, A.; Dietrich, D.R.; Sivonen, K.; Salmaso, N.
Abstract: In order to identify the cyanobacterial species responsible of anatoxin-a (ATX) production in Lake Garda (Northern Italy), an intensive isolation and culturing of filamentous cyanobacteria were established since 2014 from environmental samples. In this work, we report a detailed account of the strategy adopted, which led to the discovery of a new unexpected producer of ATX, Tychonema bourrellyi . So far, this species is the first documented example of cultured Oscillatoriales able to produce ATX isolated from pelagic freshwater ecosystems. The isolated filaments were identified adopting a polyphasic approach, which included microscopic species identification, genetic characterisation and phylogenetic analyses based on 16S rRNA genes. The taxonomic identification was further confirmed by the high (>99%) rbcLX sequence similarities of the T. bourrellyi strains of Lake Garda with those deposited in DNA sequence databases. More than half of the isolates were shown to produce a significant amount of ATX, with cell quota ranging between 0.1 and 2.6 μg mm −3, and 0.01 and 0.35 pg cell −1 . The toxic isolates were tested positive for anaC of the anatoxin-a synthetase ( ana ) gene cluster. These findings were confirmed with the discovery of one ATX producing T. bourrellyi strain isolated in Norway. This strain and a further non-ATX producing Norwegian Tychonema bornetii strain tested positive for the presence of the anaF gene of the ana gene cluster. Conversely, none of the Italian and Norwegian Tychonema strains were positive for microcystins (MCs), which was also confirmed by the absence of mcyE PCR products in all the samples analysed. This work suggests that the only reliable strategy to identify cyanotoxins producers should be based on the isolation of strains and their identification with a polyphasic approach associated to a concurrent metabolomic profiling. Graphical abstract: Highlights: We established several cultures of potentially toxic filamentous cyanobacteria. Over 50% of Tychonema in Lake Garda were shown to produce anatoxin-a (ATX). Toxin producing strains tested positive for the presence ATX coding genes. The production of ATX was confirmed also in Norwegian Tychonema spp. None of the Italian and Norwegian Tychonema cultured strains produced microcystins.